The optimisation of loading facilities at the terminal - Bagdoniene, Danute; Mazūra, Skirmantas (Transport, 2004)
In freight transportation, when a cargo is carried from one terminal to some others (or from several terminals to one area), the delay time of vehicles and loading equipment may be considerable because their operation is not well coordinated. In the presented investigation the appropriate number of transport and loading facilities to ensure their coordinated work at the terminal is determined. The problem of transportation is analysed in the terms of mass service assignment. The problems of stock management and proper choice of transport facilities are defined and analysed taking into account the relationship between the cost of transportation and vehicle capacity and the size of cargo lots. By using mathematical statistical methods, the optimal vehicle capacity is determined for a particular lot on the routes taking the cargo out as well as the periodicity of cargo delivery.First Published Online: 27 Oct 2010